Harvest maturity stage affects the concentrations of health-promoting compounds: Lupeol, mangiferin and phenolic acids in the pulp and peel of ripe ‘Kensington Pride’ mango fruit - Vithana, M.; Singh, Zora; Johnson, Stuart (Elsevier, 2019)
Mango (Mangifera indica L.) fruit is known as a good source of lupeol, mangiferin and phenolic acids. However, the effect of harvest maturity on the concentrations of these compounds in the pulp and peel of ripe ‘Kensington Pride’ mango fruit has not been reported. Thus, quantitative analysis of lupeol, mangiferin, phenolic acids and other important health-promoting compounds in the pulp and peel of ripe mango fruit harvested at four different maturity stages namely, green mature (commercial standard), sprung stage, half ripe and tree ripe was carried out. The highest concentrations of lupeol, mangiferin, vanillic acid, ferulic acid and caffeic acid in both pulp and peel and gallic acid, chlorogenic acid and total phenols in the peel were recorded in ripe fruit harvested at the sprung stage. The highest concentrations of ascorbic acid and total carotenoids in pulp and total antioxidant capacity in peel were recorded in the fruit harvested at tree ripe stage, whilst the highest antioxidant capacity in ripe pulp was recorded in those fruit harvested at half ripe stage. The sprung stage could, therefore, be considered as the best stage to harvest to obtain mango fruit with enhanced health benefits.